Cracking behavior of helium-irradiated small-volume copper. (1st April 2018) - Han, Wei-Zhong; Ding, Ming-Shuai; Shan, Zhi-Wei
Abstract: Radiation-induced grain-boundary helium bubbles are the cause of the significant helium embrittlement. However, the influence of grain-interior helium bubbles on the cracking behavior of metals has not been explored. Here, we investigate the cracking propensity of helium-irradiated small-volume Cu single-crystals, and compare with those of Cu single-crystals and Cu bicrystals. We found that the irradiation-induced helium bubbles only slightly increased the cracking propensity of the single-crystal Cu, while the cracking resistance of the helium-irradiated Cu single-crystals was superior to that of the Cu bicrystals, both with and without helium bubbles. Graphical abstract: Image 1